Full Thermal Experimental Assessment of a Dendritic Turbine Vane Cooling Scheme - Luque, S; Batstone, J; Gillespie, DRH; Povey, T; Romero, E; Asme (ASME, 2013)
A full thermal experimental assessment of a novel dendritic cooling scheme for high-pressure turbine vanes has been conducted and is presented in this paper, including comparisons to the conventional cooling arrangement for these components. The dendritic cooling system consists of cooling holes with multiple internal branches which enhance internal heat transfer and reduce the blowing ratio at hole exit. Three sets of measurements are presented, which describe, first, the local internal heat transfer coefficient of these structures, and, secondly, the cooling flow capacity requirements and overall cooling effectiveness of a highly engine-representative dendritic geometry.